Gaya Bahasa Personifikasi Dalam Novel My Beautiful Black Pearl Karya Indriyani Taslim dan Implikasi Pembelajarannya di SMA - Bayu Lintang Pangestu; Sri Mulyati; Syamsul Anwar (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research can be formulated as follows: (1) How is the use of language style, especially the style of Personification in the novel My Beautiul Black Pearl by Indriani Taslim. (2) What is the meaning of language style, especially the style of personification language found in the novel My Beautifull Black Pearl by Indriani Taslim. This research is about language style which aims to (1) Describe the style of language, especially the style of personification language in the novel My Beautiful Black Pearl by Indriani Taslim Taslim. (3) Implies the results of language style research in the novel My Beautiful Black Pearl Indriani Taslim's work in learning Indonesian in high school. The result of personification language research in the novel My Beautiful Black Pearl by Indriani Taslim received nineteen personified language style quotes. Based on the results of this study it is advisable for students to improve their ability to understand the contents of the novel in order to add insight, and on the part of the teacher it is advisable to teach more about literature appreciation. Not only that, the novel can also provide an example for students through the values ​​of life and a positive attitude from the characters in literary work.